Model of an Organization's Internal Environment Development on The Basis of Human Resource Audit - MASLOVA, Elena V.; KULCHITSKYA, Elena V.; MELYAKOVA, Evgenia V.; KIZYAN, Natalia G.; PENZINA, Olga S. (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The article deals with the theoretical aspect of an organization’s internal environment development on the basis of HR audit. An innovative approach to structuring an organization’s internal environment based on a tomographic approach is presented. Processes linking the elements of an organization’s internal environment are specified, and indicators for assessing each element are provided. The paper delivers the findings of the research of 250 Russian companies on how implementation of an HR audit influences the elements of an organization’s internal environment and their development. The authors have come to the conclusion that there is a strong correlation between the values of indicators of an organization’s internal environment and HR audit implementation. As a result of the study, an integrated model of an organization’s internal environment development on the basis of HR audit has been proposed.